Adolescent obesity incurs adult skeletal deficits in murine induced obesity model. Issue 2 (8th June 2022) - Ben Tahar, Soha; Garnier, Julien; Eller, Kerry; DiMauro, Nicole; Piet, Judith; Mehta, Shihkar; Bajpayee, Ambika G.; Shefelbine, Sandra J.
Abstract: Adolescent obesity has risen dramatically in the last few decades. While adult obesity may be osteoprotective, the effects of obesity during adolescence, which is a period of massive bone accrual, are not clear. We used a murine model of induced adolescent obesity to examine the structural, mechanical, and compositional differences between obese and healthy weight bone in 16‐week‐old female C57Bl6 mice. We also examined the effects of a return to normal weight after skeletal maturity (24 weeks old). We found obese adolescent bone exhibited decreased trabecular bone volume, increased cortical diameter, increased ultimate stress, and increased brittleness (decreased plastic energy to fracture), similar to an aging phenotype. The trabecular bone deficits remained after return to normal weight after skeletal maturity. However, after returning to normal diet, there was no difference in ultimate stress nor plastic energy to fracture between groups as the normal diet group increased ultimate stress and brittleness. Interestingly, compositional changes appeared in the former high‐fat diet mice after skeletal maturity with a lower mineral to matrix ratio compared to normal diet mice. In addition there was a trend toward increased fluorescent advanced glycation endproducts in the former high‐fat diet mice compared to normal diet mice but this did not reach significance ( p < 0.05) due to the large variability. The skeletal consequences of adolescent obesity may have lasting implications for the adult skeleton even after return to normal weight. Given the rates of adolescent obesity, skeletal health should be a concern. Abstract : High‐fat diet mice have reduced trabecular bone volume compared to normal diet mice even after returning to normal weight after skeletal maturity.